AB0933 Endocarditis in Patients Under Immunosuppressive Treatment: Don't Stop Believin'. (9th June 2015) - Pulvirenti, F.; Milito, C.; Pesce, A.M.; Quinti, I.
Abstract : Background: Patients with rheumatic disease under immunosuppressive treatment had an high risk of infection. For this subjects, infective disease could have unusual manifestation or could present as co-infection. Moreover, immunocompromised hosts could have untruthfully negative serological tests. For this reason clinicians have to search infections actively also by nested-PCR or microbial culture. Objectives: Here we describe a case of endocarditis due to coinfection by Coxiella burnetii and Borrelia burgdorferi in a patients with Systemic Lupus Erythematosus and persistent fever and relapse of arthritis, not responding to immunosuppressive therapy. This case report emphasizes the importance of excluding an infection as a cause of unusual clinical manifestation in a patient under immunosuppressive treatment. Methods: Case report. Data from medical files from a patient regularly followed up at the Immunology division of Umberto I Hospital of Rome were collected. Results: A 70-year-old female with Systemic Lupus Erythematosus had fever and chills associated with arthritis, fatigue, lymphadenopathy, skin purple lesions and erythema nodosum. The patient was under therapy with methotrexate, adalimumab and methyl prednisone because of her rheumatic disease. Fever continued despite the increase of steroid therapy and antibiotics therapy. Patient underwent to laboratory tests showed pancytopenia and high erythrocyte sedimentation rate while other inflammatory markers were normal. A skin biopsy showed dermal perivascular inflammatory infiltrate with lymphohistiocytic cells and eosinophilic and neutrophilic granulocytes. An extensive infectious diseases laboratory workup, including sets of blood cultures and serological tests, was performed with a negative outcome. A trans-thoracic echocardiogram was performed and no vegetation was remarkable; a trans-esophageal echocardiogram showed a small posterior leaflet mitral valve vegetation. The patient was tested for the main etiologic agents of culture-negative endocarditis by PCR. Because of positivity of both Coxiella burnetii and Borrelia burgdorferi DNA, Chronic Q fever and Lyme disease were diagnosed. An association of doxycycline and hydroxychloroquine was started. After 10 days the fever disappeared and the patient had a progressive improvement of arthritis and skin lesions. Co-infection between C. burneti e B. burgorferi was rarely reported but pathogenically possible because these pathogens can be transmitted by the same species of arthropods. The negative outcome of serological tests for both B. burgdorferi and C. burnetii could be related to the condition of patient's immunosoppression. Conclusions: This case report emphasizes the importance of excluding an infection as a cause of unusual arthritis. The use of PCR is mandatory in patients under immunosuppressive therapy since serological response could be missing. Disclosure of Interest: None declared